Autofotografia: um estudo de fotos e análise de possíveis mudanças na autoimagem da mulher - Savioli, Marina Pires (2022)
Women’s image has been constructed by the patriarchy, and their bodies were objectified and transformed in a product through the male gaze representation, which consequently deturped women’s bodies self-image. The male gaze influenced the construction of their image, that suffered and still suffers “pre conceptions” simply by being, reason that brings the necessity of fighting for the emancipation of the body. In the current media, aired images maintain the beauty imposition on women. In social media, we perceive a space in which can be a diffuser of a variety of representations, but what prevails is the seen image as the absolute truth. This concept reverbs on women’s image, that they see themselves again inside a social mold. Therefore, possibilities of the emancipation of the body were studied through autophoto, as a means of empowerment and reconnection between their internal and external images, this time expressed, not repressed. To analyze new forms of expression of the women’s body, analyses were made of autophotographys of photographers like Francesca Woodman and Danny Bittencourt, with the contribution of image concepts from important authors, like Flusser, Baitello, Belting, Barthes and Byung-Chul Han